Smart Fluorosurfactant‐Assisted Microfluidics Powered On‐Demand Generation and Retrieval of Cell‐Laden Microgels - Xiangke Li; Helen Forgham; Qiuren Shen; Liwen Zhang; Christoph Meinert; Chun‐Xia Zhao; Yiliang Lin; Dan Yuan; Thomas P. Davis; Ruirui Qiao (Advanced Materials Interfaces, 2025)
Abstract Microfluidics have been widely employed as powerful tools to fabricate monodisperse, cell‐laden hydrogel microdroplets with precise control for various biological applications, particularly in tissue engineering. While these systems enable high‐throughput production of uniform microgel particles, the encapsulation and stabilization of water‐in‐oil hydrogel emulsions often require surfactants to reduce the surface tension of the microgel droplets. However, these surfactants must be removed with chemical demulsifiers to retrieve the cell‐laden microgels for downstream applications, which often leads to toxic effects on the cells. Herein, a novel class of thermo‐responsive “smart” surfactants is reported for on‐demand demulsification of microfluidic droplets. These surfactants are synthesized by coupling perfluoropolyethers (PFPEs) with a thermo‐responsive block of N‐isopropylacrylamide (NIPAM) using reversible addition‐fragmentation chain transfer (RAFT) polymerization. The resulting P(NIPAM)n‐PFPE surfactants exhibited temperature‐dependent amphiphilicity, enabling stabilization of water‐in‐oil droplets at low temperatures and destabilization at elevated temperatures. This approach offers a non‐invasive and biocompatible method for microgel recovery without the need for harmful chemical demulsifiers or additional processing steps. The combination of precise control over surfactant properties and thermo‐responsive behavior opens new avenues for developing smart, biocompatible emulsion systems for advanced droplet microfluidics applications in tissue engineering, drug delivery, and single‐cell analysis.